Generation z’s interior design perceptions and responses to selected coffee shops (quick-service restaurants) - Danganan, Trisha Janna A.; Magbuhos, Victoria Marielle S.; Juarez, Lizza Magdalena E. (Quezon City University of the Philippines Diliman, 2025)
Coffee shop quick-service restaurants (QSRs), a part of MSMEs, are shifting to cater to the Generation Z, a rising key consumer group in the coffee shop QSR landscape. This qualitative descriptive study identified the existing interior design elements (color and light) and features (furniture and built-in fixtures) of a selected coffee shop QSR, and investigated how it was perceived by Gen Z consumers. Three branches of the QSR were purposively selected along with 10 Gen Z students from each branch, resulting in a total of 30 respondents for the study. Ocular and observation forms were used to gather data for interior design elements and features, and online surveys were conducted for the Gen Z perception. Data analysis was done through content and descriptive analysis. Findings show that the QSRs had light analogous and monochromatic color schemes, alongside natural and artificial lighting. The furniture consisted of non-cushioned stools, benches and upholstered banquette seating, along with built-in service counters that had linear layouts and various finishing materials. Gen Z respondents positively perceived the color schemes and different types of lighting. However, they found the non-cushioned seats uncomfortable, and while the service counters had an efficient flow, they were not visually appealing for them. It was found that most respondents were likely to revisit the QSRs specifically because of the interior design elements present. Overall, the sensory experience related to the visual interior design elements was positive. However, the physical interior design features could use improvement, as respondents indicated a need for more upholstered seating in a larger dining space and for the restaurant’s brand identity to be more visible and consistent at the service counters. Future research can consider using other interior design elements and features, and other F&B establishments using a wider range of respondents.
In partial fulfillment for the Degree of Bachelor of Science in Interior Design
Thesis
Keywords: Coffeehouses -- Philippines; Interior decoration; Generation Z; Coffee shops -- Philippines; Quick-service restaurants; Fast food restaurants; Interior lighting